Olfactory Consciousness across Disciplines - Benjamin D. Young (Frontiers Research Topics, 2015)
Our sense of smell pervasively influences our most common behaviors and daily experience, yet little is known about olfactory consciousness. Over the past decade and a half research in both the fields of Consciousness Studies and Olfaction has blossomed, however, olfactory consciousness has received little to no attention. The olfactory systems unique anatomy, functional organization, sensory processes, and perceptual experiences offers a fecund area for exploring all aspects of consciousness, as well as a external perspective for re-examining the assumptions of contemporary theories of consciousness. It has even been suggested that the olfactory system may represent the minimal neuroanatomy that is required for conscious processing. Given the variegated nature of research on consciousness, we include original papers concerning the nature of olfactory consciousness. The scope of the special edition widely incorporates olfaction as it relates to Consciousness, Awareness, Attention, Phenomenal- or Access-Consciousness, and Qualia. Research concerning olfaction and cross-modal integration as it relates to conscious experience is also address. As the initial foray into this uncharted area of research, we include contributions from across all disciplines contributing to cognitive neuroscience, including neurobiology, neurology, psychology, philosophy, linguistics, and computer sciences. It is our hope that this Research Topic will serve as the impetus for future interdisciplinary research on olfaction and consciousness.